Mechanical and biological evaluations of smart antibacterial nanostructured TI-6AL-7NB implant / Alireza Rafieerad - Alireza , Rafieerad (2017)
Increased demands of artificial bone let the severe plastic deformation (SPD)-processed titanium bioalloys to be widely used as orthopedic and dental implants due to appropriate mechanical, tribocorrosion and biological properties. Based on the literature available on laboratory and animal studies, the related β-type substrates can provide higher bone functionality with some economic limitations. In this study, biomedical grade of near β Ti-6Al-7Nb alloy (Ti67IMP) was selected as implant substrate. Nevertheless, these metallic prosthesis still cannot meet all requirements and surface modifications that are required to promote the biofunctionality and minimize failure risk. Hence, multilayer metallic/ceramics/carbon-based topographies were developed to improve Ti67IMP performance. Application of Taguchi design of experiments (DOE) and multi-objective particle swarm optimization employed to maximize the coating outputs. Highly ordered mixed oxides TiO2-Nb2O5-Al2O3 nanotubes anodically grown on as-deposited physical vapor deposition (PVD) niobium (Nb)/Ti67IMP surface. Synthesized few-layered graphene oxide (GO), concentrations of silver nanoparticles decorated GO (AgNPs-GO) and thermally exfoliated mono-layer graphene (TGr) functionalized arginine amino acid (Arg-Gr) transparently spin-coated tubular film. Microstructural features of layer-by-layer have been analyzed by physicochemical characterizations. The mechanical, corrosion, wettability and in-vitro bioactivity properties of designed surfaces were assessed as well antibacterial activity against cultured Gram-negative bacteria e.g. Escherichia coli (E. coli) and Gram-positive e.g. Staphylococcus aureus (S. aureus). Moreover, biocompatibility interaction of seeded human osteoblast (hFOB) cells checked after 1, 3, 5 and 7 day bioassay proliferation. Quantitative and quantitative cytotoxicity, cell growth, adhesion and morphology followed to determine the bone implant feasibility of biostructures. From the results, thick bone-like apatite layers successfully formed on treated Ti67IMP surfaces. The poor antibacterial ability of GO martial limited its application. Besides, the distributed non-degradable AgNPs increased the toxicity trend affected by concentration within culture time. The competitive bactericidal ability of non-expensive organic large-area Arg-Gr biomorphology in compare with risky AgNPs was highlighted. Superior mechanical stability of single-layer TGr attached functional groups rather than defected GO increase hardness and corrosion resistance of bare Ti67IMP from 1.795 to 5.345 GPa and 7.719×10-1 to 3.743×10-7 mm year-1 respectively. In a nutshell, the reasonable introducing of smart bioactive antibacterial Arg-Gr/mixed oxides/Nb/Ti67IMP composite-implant system with enhanced characteristics and drug delivery potential may contribute to facilitate rapid osseointegration and long-term replacement without infection signs.